2010
DOI: 10.1039/c001584a
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide/actinide differentiation with sterically encumbered N-heterocyclic carbene ligands

Abstract: A study is reported on the relative stability of trivalent bis(ligand) complexes of the form [M(L(R))(2)N''] for trivalent group 3, lanthanide and actinide cations, using the sterically demanding N-heterocyclic carbene ligand L(R) = [OCMe(2)CH(2){CNCH(2)CH(2)NR}] (R = (i)Pr L(P), Mes L(M), Dipp L(D); N'' = N(SiMe(3))(2)). For the small Y(III) cation (r(6-coord) = 1.040 A) and the smallest L(R), R = (i)Pr, mono, bis, and tris(L(P)) complexes can be made; [Y(L(P))(2)N''] and [Y(L(P))(3)] have been characterised.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…N -heterocyclic carbene ligands are well-known for their strongly σ-donating character and have found utility in stabilizing high-valent transition metal complexes, homogeneous catalysis, and even actinide–lanthanide differentiation . However, N -heterocyclic carbene complexes of the f-elements are still fairly sparse, found primarily in heteroleptic systems in which the carbene is tethered to an alkyl chain or stabilized by bulky heteroatom substituents .…”
Section: Resultsmentioning
confidence: 99%
“…N -heterocyclic carbene ligands are well-known for their strongly σ-donating character and have found utility in stabilizing high-valent transition metal complexes, homogeneous catalysis, and even actinide–lanthanide differentiation . However, N -heterocyclic carbene complexes of the f-elements are still fairly sparse, found primarily in heteroleptic systems in which the carbene is tethered to an alkyl chain or stabilized by bulky heteroatom substituents .…”
Section: Resultsmentioning
confidence: 99%
“…There are several review articles reported in the past decade, which are dedicated to NHC ligands bearing one additional donor group [ 7 , 8 , 9 , 10 ]. Included in these review articles are bidentate NHC ligands with phosphorous tether [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], nitrogen [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and oxygen tethers [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Introductionmentioning
confidence: 99%
“…However, since previous studies showed that these complexes can be quite challenging in their synthesis, we sought for NHC ligands with anionic linker atoms, which facilitate the metal binding of the NHC ligand and enforce a stronger bonding of the NHC to the metal center. Employing this strategy has led to the isolation of various unusual main group, early transition metal, late transition metal , and f-element NHC complexes with unique reactivity patterns and spectroscopic as well as electrochemical properties. In our search for a NHC ligand that is capable of forcing the metal center to bind to the NHC moiety by using anionic linker groups, we came across the bis-phenol benzimidazolium chloride [H 3 L 1 ]­Cl introduced by Bercaw et al and by Bellemin-Lapponnaz .…”
Section: Introductionmentioning
confidence: 99%